Pengaruh Financial Distress dan Cash Holdings Terhadap Manajemen Laba dengan Kepemilikan Manajerial Sebagai Variable Moderasi : Studi Empiris Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) - Juanita Marissa Prayitno; Muhammad Ali Ma`Sum (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
Earnings management practices remain a concern due to their potential to diminish the quality of financial statements and influence stakeholder decision-making. This study aims to analyze the impact of financial distress and cash holdings on earnings management, with managerial ownership serving as a moderating variable and leverage as a control variable, focusing on manufacturing companies listed on the Indonesia Stock Exchange during the 2022–2024 period. A quantitative approach was employed using secondary data derived from annual financial reports. The sample was selected using a purposive sampling technique, resulting in 89 companies and 267 observations. Data analysis was conducted using panel data regression with the aid of EViews 13. The results indicate that financial distress has a significant negative effect on earnings management, whereas cash holdings and leverage have a significant positive effect. Managerial ownership was found to moderate the relationship between financial distress and earnings management by weakening the impact of financial distress; however, it did not moderate the relationship between cash holdings and earnings management. These findings demonstrate that financial pressure, corporate liquidity, and financing structures influence earnings management practices, while the effectiveness of managerial ownership as a corporate governance mechanism depends on the specific conditions faced by the company. This study provides empirical evidence regarding the role of managerial ownership in moderating earnings management practices within Indonesian manufacturing companies.